Strategi Komunikasi Pemerintah Kota Salatiga dalam Upaya Pencegahan Penyebaran COVID-19 - Elisa Husein; Rini Darmastuti; Richard Gordon Mayopu (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2021)
Information about COVID-19 became an urgency for every individuals in this pandemic situation. Unfortunately, not all of the information were told in the appropriate communication strategy, it raised some unwanted impacts, such as fear and anger. Pace, Paterson, and Burnett, stated that communication strategy has three main purposes. This paper tried to dig up and describe the communication strategy of Salatiga City Government in their effort to prevent the spread of COVID-19 in Salatiga. The results are first, the informations about COVID-19 are delivered with video, poster, and others. Second, the strategy used gave impacts on changes in affective, cognitive and behavior. Third, this strategy could be made in a communication strategy model which emphasized in the source credibility, clarity of content, and interesting medias. The research revealed that this strategy hadn’t built a full awareness of the society, one of the causes was the lack of even information delivered to the Salatiga society. Therefore, Salatiga City Government’s communication strategy could be improved in order to be an effective communication strategy.